Effect of Glutamine Supplement Administration on the Reduction of Muscular Fatigue Post-Eccentric Exercise - Rusdiawan, Afif; Taufikkurrachman, Taufikkurrachman (Folia Medica Indonesiana, 2019)
Menopausal period is the period of permanent cessation of menstruation due to reduced or lost ovarian activity. One of the effects of decline estrogen levels during menopause is atropic vulvovaginitis. Consumption of phytoestrogens can reduce menopausal symptoms. Phytoestrogen is found in vegetables and fruits such as tomatoes and red melon. The objective of this study was to compare the effectiveness of red melon juice and tomato on the increase of vaginal wall thickness in menopausal rats. This study revealed an alternative of phytoestrogen sources that is more effective to reduce menopausal symptoms, especially those related to vaginal atrophy to improve the quality of life of menopausal women. Subjects of this study were 27 ovariectomized Wistar strain Rattus norvegicus which were s divided into 3 groups randomly, one control group and two treatment groups with tomato juice and red melon juice at a dose of 330 mg/kgBW/day administered for 28 days. The variable of this study were the thickness of the vaginal wall which was precipitated by Hematoxiline Eosine. The highest vaginal wall thickness was found in the treatment group of red melon juice of 879.89 ± 70.52 µm and the lowest of the control group (K) of 643.3 ± 58.33 µm. The results of Anova test showed that there was a significant difference between control group and treatment groups, the tomato juice and red melon juice with a dose of 330 mg/kgBW/day, so it can be concluded that red melon juice with a dose of 330mg/Kg BW/day has the best effect in increasing the thickness of vaginal wall of menopausal rats as compared with tomato juice.